Hungarian higher education EFL students’ perceptions of learner autonomy - Win, Cho Cho; Kálmán, Csaba (Glottodidactica, 2023)
Technology has provided language learners with opportunities to learn English autonomously. Despite previous studies in the Hungarian context (e.g., Édes 2008; Szőcs 2017), more research on learner autonomy is required in order to find out what might explain university EFL learners’ lack of autonomy and help them become more autonomous. The purpose of this quantitative study was to address the problem by investigating learners’ perceptions of their own and their teachers’ responsibilities in language learning, their perceived abilities and motivation to learn English, their autonomous behaviours outside and inside the classroom, and the relationships between the above variables. The questionnaire was completed by 74 EFL students from a Hungarian university. The data were analysed by SPSS 26.0. The results indicate that in the investigated context, in the EFL learners’ perceptions, teachers were more responsible for their in-class learning than themselves. Nevertheless, the students demonstrated some autonomy both inside and outside class, to an equal extent.